Missões em Hainan (1891)
This 1891 diplomatic despatch, authored by Demetrio Cinatti, Consul of Portugal in Canton, constitutes a formal protest addressed to Sir Ly, Viceroy of the Two Guangs under the Qing Dynasty, concerning the destruction of Portuguese missionary properties in Hainan during civil disturbances in 1884. The document details the legal and historical grounds upon which the Portuguese mission’s claim for restitution is based, refuting Chinese provincial authorities’ assertions that the destroyed chapels were locally owned Christian structures dating from the Ming dynasty. Drawing on ecclesiastical law, treaty obligations, and empirical evidence—including financial records, prior compensation precedents, and official correspondence—the consul demonstrates that the chapels in Giang-tó (Siang-tô) and Wang-fo were constructed in 1795 by Portuguese missionaries on legally acquired land, maintained through foreign ecclesiastical funding, and remained under the exclusive ownership of the Catholic Church. The text further establishes that local officials were fully aware of these institutions, citing administrative actions from 1854 and 1880 as proof of official recognition. It condemns the Hainan authorities’ failure to protect the properties despite treaty guarantees, their fabrication of local consent, and their contradictory claims regarding the events. The despatch also invokes Portugal’s strict neutrality during the Sino-French War (1883–1885), contrasting it with the targeting of its missionaries, and appeals to the Viceroy’s sense of justice and diplomatic reciprocity in demanding full reparations.
5
Keywords: Catholic Church jurisdiction; Civil Disturbances; Colonial Legal Claims; Consul Demétrio Cinatti; Consular Diplomacy; Ecclesiastical Law; Foreign Funding; Foreign Property Protection; Formal Protest; Giang-tó chapels; Guangdong governance; Hainan chapels; Land Ownership; Ming dynasty records; Official Recognition; Portuguese missionary properties; Prior Compensation; Provincial Authorities Denial; Qing Dynasty; Religious Site Destruction; Restitution Claim; Transcription; Treaty Obligations; Viceroy Sir Ly; Wang Fo chapels; late Qing China